Development of modules based on project-based learning material on block nets and cubes - Aliza Wulandari; Siti Quratul Ain; Fitriana Yolanda (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2024)
The project-based module learning model is one learning method that follows current technological developments. This model is an innovative and student-centered learning approach and aims to improve student learning outcomes. The project-based learning module developed aims to improve students' abilities in solving project problems so that students can complete the module containing this project. The research aims to create a project-based learning module for class IV block and cube network materials. This research is research and development using qualitative and quantitative approaches. The method used is Research and Development with a 4D model. The 4D model consists of four main steps. The first step is to define, which involves determining the product to be developed. The second step is design, which involves creating a predetermined product design. The third step is development. Material, design, and language experts are given questionnaires for module testing. Data was evaluated using a Likert scale. The validation results showed that material experts received 82.9 percent of presentations in the very appropriate category, design experts received 81.2 percent, and language experts received 83.1 percent of presentations in the very appropriate category. AbstrakSalah satu metode pembelajaran yang mengikuti perkembangan teknologi saat ini adalah model pembelajaran modul berbasis proyek. Model ini adalah pendekatan pembelajaran yang inovatif dan berpusat pada peserta didik dan bertujuan untuk meningkatkan hasil belajar siswa. Tujuan penelitian adalah untuk membuat modul pembelajaran berbasis proyek untuk materi jaring balok dan kubus kelas IV. Modul project-based learning yang dikembangkan bertujuan untuk meningkatkan kemampuan peserta didik dalam pemecahan masalah proyek, sehingga modul berisi proyek ini dapat diselesaikan oleh peserta didik. Metode penelitian ini adalah penelitian dan pengembangan menggunakan pendekatan kualitatif dan kuantitatif. Metode yang digunakan ialah Research and Development dengan model 4D. Model 4D terdiri dari empat langkah utama, yaitu: define, yang melibatkan penentuan produk yang akan dikembangkan. Langkah kedua adalah design, yang melibatkan pembuatan desain produk yang telah ditentukan sebelumnya. Langkah ketiga adalah development, angket diberikan kepada ahli materi, ahli desain, dan ahli bahasa untuk pengujian modul. Data dievaluasi dengan skala likert. Hasil validasi menunjukkan bahwa ahli materi mendapatkan presentasi 82,9 persen kategori sangat layak, ahli desain mendapatkan presentasi 81,2 persen kategori sangat layak, dan ahli bahasa mendapatkan presentasi 83,1 persen kategori sangat layak.Kata Kunci: media pembelajaran; modul; pembelajaran berbasis proyek